Additive Eigenvalue Problems of the Laplace Operator with the Prescribed Contact Angle Boundary Condition. (28th April 2020) - Li, Hongmei; Wang, Peihe
Abstract : Additive eigenvalue problem appears in ergodic optimal control or the homogenization of Hamilton–Jacobi equations. It has wide applications in several fields including computer science and then attracts the attention. In this paper, we consider the Poisson equations with the prescribed contact angle boundary condition and finally derive the existence and the uniqueness of the solution to the additive problem of the Laplace operator with the prescribed contact angle boundary condition.